Adjustment for Atherosclerosis Diagnosis Distorts the Effects of Percutaneous Coronary Intervention and the Ranking of Hospital Performance. Issue 11 (23 September 0207) - Niknam, Bijan A.; Arriaga, Alexander F.; Rosenbaum, Paul R.; Hill, Alexander S.; Ross, Richard N.; Even‐Shoshan, Orit; Romano, Patrick S.; Silber, Jeffrey H.
Abstract : Background: Coronary atherosclerosis raises the risk of acute myocardial infarction (AMI), and is usually included in AMI risk‐adjustment models. Percutaneous coronary intervention (PCI) does not cause atherosclerosis, but may contribute to the notation of atherosclerosis in administrative claims. We investigated how adjustment for atherosclerosis affects rankings of hospitals that perform PCI. Methods and Results: This was a retrospective cohort study of 414 715 Medicare beneficiaries hospitalized for AMI between 2009 and 2011. The outcome was 30‐day mortality. Regression models determined the association between patient characteristics and mortality. Rankings of the 100 largest PCI and non‐PCI hospitals were assessed with and without atherosclerosis adjustment. Patients admitted to PCI hospitals or receiving interventional cardiology more frequently had an atherosclerosis diagnosis. In adjustment models, atherosclerosis was associated, implausibly, with a 42% reduction in odds of mortality (odds ratio=0.58, P <0.0001). Without adjustment for atherosclerosis, the number of expected lives saved by PCI hospitals increased by 62% ( P <0.001). Hospital rankings also changed: 72 of the 100 largest PCI hospitals had better ranks without atherosclerosis adjustment, while 77 of the largest non‐PCI hospitals had worse ranks ( P <0.001). Conclusions: Atherosclerosis is almost always noted in patients with AMI who undergo interventional cardiology but less often in medically managed patients, so adjustment for its notation likely removes part of the effect of interventional treatment. Therefore, hospitals performing more extensive imaging and more PCIs have higher atherosclerosis diagnosis rates, making their patients appear healthier and artificially reducing the expected mortality rate against which they are benchmarked. Thus, atherosclerosis adjustment is detrimental to hospitals providing more thorough AMI care.